2006
DOI: 10.1007/s10291-005-0019-z
|View full text |Cite
|
Sign up to set email alerts
|

Estimating atmospheric pressure loading regression coefficients from GPS observations

Abstract: ERRATUMThe online version of the article can be found at http://www.dx

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0

Year Published

2007
2007
2020
2020

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 18 publications
1
7
0
Order By: Relevance
“…The pressure anomaly range is large at the high latitude under consideration, with an overall peak to peak maximum of over 70 hPa during the study and a maximum daily range of 40 hPa. These values are very similar to those experienced at high northern latitudes (Kaniuth and Vetter, 2006).…”
Section: Analysis Of Vertical Motions In Gps Time-seriessupporting
confidence: 84%
See 1 more Smart Citation
“…The pressure anomaly range is large at the high latitude under consideration, with an overall peak to peak maximum of over 70 hPa during the study and a maximum daily range of 40 hPa. These values are very similar to those experienced at high northern latitudes (Kaniuth and Vetter, 2006).…”
Section: Analysis Of Vertical Motions In Gps Time-seriessupporting
confidence: 84%
“…As pressure changes the tropospheric delay estimates vary. This could show up in the GPS time-series as height changes, which could be wrongly interpreted as the response to local load changes (Kaniuth and Vetter, 2006). We use relative antenna phase center variation tables from NGS and the Niell Mapping Function (Niell, 1996) when processing Cape Roberts.…”
Section: Introductionmentioning
confidence: 99%
“…Similar results were obtained for GPS . Linear ATML regression coefficients between vertical site displacements and local pressure variations have been derived as estimable quantities from VLBI (MacMillan and Gipson, 1994) and GPS observations (Kaniuth and Vetter, 2005). Their results reveal an improved baseline length repeatability but also demonstrate the limitations of fitting local pressure variations to deformation caused by regional pressure anomalies.…”
Section: Geodetic Conceptmentioning
confidence: 97%
“…Geodetic time series recorded by the Global Positioning System (GPS) have revealed that surface load variations can induce measurable surface strain. Variations of surface loading can result from various sources: tidal loading [ Agnew , , ], continental water storage [ Blewitt et al , ; Bevis et al , ; Van Dam et al , ; Davis et al , ; Bettinelli et al , ; Steckler et al , ; Elósegui et al , ; Fu and Freymueller , ; Fu et al , ; Wahr et al , ], ice and snow [ Grapenthin et al , ; Matsuo and Heki , ; Jiang et al , ], and atmospheric pressure [ Kaniuth and Vetter , ]. The analysis of these signals has attracted much attention.…”
Section: Introductionmentioning
confidence: 99%